HUMAN RESOURCE INFORMATION SYSTEM AS A MODERATING VARIABLE OF THE INFLUENCE OF LEADERSHIP STYLE VARIABLES ON EMPLOYEE PERFORMANCE - Rezky Amalia Hamka; Lenny M Possumah; Fitri Devi; Asmita Wulansari Dgn Liwang; Adrian Polim (JURNAL ILMIAH EDUNOMIKA, 2025)
Abstract This study is a quantitative study with an explanatory approach, namely an approach that relies on a number of previous studies to build a framework that researchers formulate in the hypothesis section and prove it. The data used in this article is primary data that researchers obtained from 350 Superindo employees. The data obtained were analyzed using the smart PLS 4.0 analysis tool. The result in this article show the Leadership Style variable can have a positive relationship direction and a significant influence on Employee Performance and the Human Resource Information System variable can moderate the influence of the Leadership Style variable on Employee Performance because the P-Values ​​are positive and below the significance level of 0.05, namely 0.018. In addition, the Human Resource Information System variable can moderate the influence of the Leadership Style variable on Employee Performance because the P-Values ​​are below the significance level of 0.05, namely 0.000, more significant than direct testing. Thus it can be concluded that the first and second hypotheses in this article can be proven. Keywords: Leadership Style, Employee Perdormance, Human Resource Information System